Polyelectrolyte Surface Interface for Single-Molecule Fluorescence Studies of DNA Polymerase. (March 2003) - Kartalov, Emil P.; Unger, Marc A.; Quake, Stephen R.
We report the use of polyelectrolyte multilayers in a stable robust surface chemistry for specific anchoring of DNA to glass. The nonspecific binding of fluorescently tagged nucleotides is suppressed down to the single-molecule level, and DNA polymerase is active on the anchored DNA template. This surface-chemistry platform can be used for single-molecule studies of DNA and DNA polymerase and may be more broadly applicable for other situations in which it is important to have specific biomolecular surface chemistry with extremely low nonspecific binding.